AMOURINS SHELLMOUND: UNCOVERING BIODIVERSITY AND CHRONOLOGY THROUGH CHARCOAL ANALYSES. Issue 4 (2nd August 2021) - Macario, Kita D; Scheel-Ybert, Rita; Ribeiro-Pinto, Natacha; Pereira, Bruna B; Amaral, Dayanne; Alves, Eduardo Q
ABSTRACT: In paleoenvironmental research, several proxies are used to reconstruct climate and vegetation. The establishment of a chronological framework allows for the association of different proxies and correlation of events happening in different geographic areas. Cultural deposits, such as the shellmounds found along the coast of Brazil, play an important role in paleoenvironmental interpretations. Here, we have employed anthracological analysis in charcoal fragments from the Amourins shellmound, located at the margins of the Guanabara Bay, Rio de Janeiro. This allowed for the taxonomic identification and selection of short-lived trees and specific parts of plants for accurate radiocarbon dating. We recorded genera and families typical of the Atlantic Forest, restinga forest, open restinga and mangrove. The 14 C ages of charred nuts from different occupational layers range from 3807 ± 35 to 3503 ± 70 BP and a sequential chronological model was built, relating the predominance of mangrove vegetation to the period between 4130–3960 cal BP.